PENERAPAN METODE DISCOVERY LEARNING MELALUI TEKNIK “BARENDISTUP” DALAM PEMBELAJARAN MENULIS TEKS ULASAN CERPEN - Karnengsih, Euis (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
This study aims to apply the methods of discovery leraning through the technique of "barendistup" in learning to write the text review the short stories in Class VIII students of SMP Negeri 5 Tuban in academic year 2015/2016. In this study are described (1) the validity of the design of learning to write the text reviews the short story by the method of discovery learning through techniques "Barendistup" in class VIII SMPN 5 Tuban Academic Year 2015/2016 which includes a scenario, materials, media, and assessment of learning; (2) the practicality of the implementation of learning to write short stories that includes text reviews the activities of teachers and students in learning activities; and (3) the effectiveness of learning outcomes covering aspects of attitudes, knowledge, and skills. The method used in this research is applied research.